From Emergency to Regulation: Agenda Setting for Indonesia's Covid-19 Policy Through the Perspectives of Govermentality and the Policy Cycle - Putri Khairunnsia Bekti; Welsa Aswita; Abdal (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
AbstractThe COVID-19 pandemic prompted the Indonesian government to immediately take various policy measures in response to the health crisis, which had become a more complex problem. However, this policy agenda-setting process is not simply viewed as a simple response to public health issues, but also as a result of broader governmental rationality. This study aims to analyze how agenda-setting in COVID-19 policy in Indonesia occurs by combining the policy cycle perspective and Michael Foucault's concept of governmentality. The method chosen is descriptive qualitative research with a literature review approach, utilizing government policy documents, academic sources, and ongoing previous studies. The analysis focuses on the formation of the policy agenda, starting with the establishment of the COVID-19 Task Force and continuing through the implementation process involving various regulations for handling the pandemic throughout 2020. The research findings indicate that the pandemic was successfully elevated to the government agenda as a public issue requiring a rapid response, but also necessitating policy development that proceeded not solely based on public health logic. The government has classified COVID-19 as a national emergency and a non-natural disaster, allowing for expanded state intervention through various social, economic, and security regulatory instruments. This study concludes that the establishment of the COVID-19 policy agenda in Indonesia is the result of the interaction between the need to address the health crisis and the rationality of power exercised through population management mechanisms. Incorporating a governmentality perspective into policy cycle analysis provides a more comprehensive understanding of the relationship between power, knowledge, and the public policymaking process.Keywords: COVID-19, agenda setting, policy cycle, governmentalit y, public policy, Indonesia.